2012
DOI: 10.1007/s00784-012-0736-y
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion of nano-hybrid resin-based composites with novel and conventional matrix formulation

Abstract: For the tested RBCs, increments of 2 mm and irradiation time of at least 20 s may be recommended for clinical practice. The two materials containing novel monomer composition might be applied for enlarged increments because of the low decrease of DC they demonstrated for 6-mm increments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
(66 reference statements)
2
28
0
1
Order By: Relevance
“…Degree of conversion of BioSeal ® presented no significant difference compared to Defense Chroma ® . Their results are comparable to other experimental and commercial adhesives 13 , sealants 14 and composite resins 15 . Although sealants had different filler particles, they showed no difference in polymerization behavior, such as previously results, also evaluating other resin-based materials 16 .…”
Section: Discussionsupporting
confidence: 72%
“…Degree of conversion of BioSeal ® presented no significant difference compared to Defense Chroma ® . Their results are comparable to other experimental and commercial adhesives 13 , sealants 14 and composite resins 15 . Although sealants had different filler particles, they showed no difference in polymerization behavior, such as previously results, also evaluating other resin-based materials 16 .…”
Section: Discussionsupporting
confidence: 72%
“…Durner et al and Frauscher et al concluded that adequate curing time (20 s, 40 s) with a moderate irradiance (ca. 1000 mW/cm 2 ) is essential to ensure that the resin composite is adequately polymerized; as an extended curing time (more than 40 s) resulted in a significant increase in DC and a short curing time (5 s, 10 s) resulted in a lower DC [31,32]. DC 4mm is a valuable property in characterising changes within one material.…”
Section: Discussionmentioning
confidence: 98%
“…However, the high post-cure increase in the DC for 0-ACP evened out the differences after 72 h. Disparate refractive indices (RIs) of resin and fillers make materials appear opalescent and increase light scattering within the material, whereas similar RIs contribute to translucency and improve light conduction (33). Presumably, the RIs of the resin matrix and barium-glass fillers were well matched.…”
Section: Discussionmentioning
confidence: 99%
“…If well dispersed in the composite, nanoparticles do not contribute to scattering (35). However, this is often not the case, since they tend to agglomerate (33). Despite the efforts to achieve homogenous filler particle distribution in all composite pastes, filler clusters in Si-ACP might have been formed due to agglomeration tendency of both ACP and silica, but also due to the relatively high amount of silica fillers.…”
Section: Discussionmentioning
confidence: 99%